Determinants of the level of indebtedness for Brazilian firms: A quantile regression approach - Guilherme Resende Oliveira; Benjamin Miranda Tabak; José Guilherme de Lara Resende; Daniel Oliviera Cajueiro (EconomiA, 2013)
We investigate the determinants of the capital structure of Brazilian companies between 2000 and 2009. We use a quantile regression model and compare its results with the ones provided by conventional models (least squares and fixed effects). We show that the effects of the capital structure determinants change depending on the quantile. This can be explained by bankruptcy and agency costs associated to the amount of debt leverage of firms, relative to each quantile. Based on these results, we analyze the predicted effects of the two leading capital structure theories, namely pecking order and trade-off, conditioned on the determinant, type of debt and quantile analyzed. Our results for the size and profitability variables indicate that the pecking order theory is more suitable to the data as the quantile increases. – – Este estudo examina os determinantes da estrutura de capital das empresas brasileiras entre os anos de 2000 e 2009. Nós usamos um modelo de regress\~ao quantílica e comparamos seus resultados com aqueles fornecidos por modelos convencionais (mínimos quadrados e efeitos fixos). Nós obtemos um melhor entendimento da estrutura de capital de empresas Brasileiras. Nós mostramos que os efeitos dos determinantes da estrutura de capital variam com o quantil analisado. Essa influência pode ser explicada por custos de falência e agência associados ao nível de endividamento das empresas, em cada quantil. Tomando como base esses resultados, nós analisamos as previs\~oes dos efeitos das principais teorias da estrutura de capital, pecking order e trade-off, dependendo do determinante, tipo de dívida e quantil analisado. Nossos resultados para as variáveis tamanho e lucratividade mostram que a teoria da pecking order se torna mais relevante à medida que os quantis aumentam.
Keywords: G3; G32; G34; C21; 330; Capital structure; Quantile regression; Pecking-order; Trade-of